Measuring the Coagulability of Fibrinogen in Plasma by Isotopic Means - Regoeczi, E. (Thrombosis and Haemostasis, 1967)
1. A simple and reproducible technique for measuring the clottability of plasma fibrinogen using iodinated fibrinogen is described, the coefficient of variance being less than 1 %.2. In vivo experiments in rabbits and monkeys on one hand and in vitro studies with fibrinogens from various species on the other indicated that :a) Aliquots of a fibrinogen preparation iodinated at the same mean substitution level yield practically identical coagulabilities ;b) Aliquots of one labelled preparation when injected into several healthy animals or mixed with their plasmas give equal values for clottability;c) In normal animals, the clottable proportion of the circulating protein-bound radioactivity is at any time a function of the extra/intravascular distribution and of the catabolic rate of fibrinogen relative to the corresponding values of the contaminating labelled protein.3. The significance of the behaviour of the non-clottable protein-bound radioactivities during fibrinogen turnover experiments for the catabolic mechanism is discussed. It is suggested that fibrinogen catabolism is probably an intracellular process.